A curious case of attempted infanticide by percutaneous needles insertion: diagnosis and laparoscopic management. - Meriem Braiki; Mongi Mekki; Besma Gafsi; Amine Ksia (Pediatric Surgery Research Center of Shahid Beheshti University of Medical Sciences, 2017)
This is the case of a 6 month-old boy victim of an attempted infanticide by means of sharp long needles inserted through the abdominal wall. He was successfully managed by laparoscopic approach.